1999
DOI: 10.1097/00009957-199910000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Radiologic Morphology of the Bone Lengthening Formation and Its Complications

Abstract: SUMMARYThe objective was to study the different types of lengthened bone regeneration and their development during the various phases of the process to correlate them with patient factors and the surgical technique used, and to establish a possible relation between the development of the bone lengthening formation and the problems or complications. The authors studied the radiographs of a random group of 55 patients taken at three points during the course of treatment. The callus was classified with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, the greatest problem remains the long healing time. External fixation carries the risk of pin tract infection, malalignment, joint stiffness, and late fracture of the regenerate [8,9,22]. Shortening of the period of external fixation would reduce costs, complications, and the burden on the patient.…”
Section: Introductionmentioning
confidence: 99%
“…However, the greatest problem remains the long healing time. External fixation carries the risk of pin tract infection, malalignment, joint stiffness, and late fracture of the regenerate [8,9,22]. Shortening of the period of external fixation would reduce costs, complications, and the burden on the patient.…”
Section: Introductionmentioning
confidence: 99%
“…AP (c) and lateral (d) radiographs at presentation of the regenerate collapse moderately above chance. This high variability as to when surgeons find it appropriate to remove an external fixator may contribute, along with other factors (such as primary diagnosis), to the large cited rate of refracture after frame removal (3% to 50%) [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Starr et al [17] found that the decision to remove an external fixator based on radiographic assessment alone resulted in intra-observer and inter-observer variability moderately above chance. This high variability as to when surgeons find it appropriate to remove an external fixator may contribute, along with other factors (such as primary diagnosis), to the large cited rate of refracture after frame removal (3% to 50%) [1822].…”
Section: Introductionmentioning
confidence: 99%